2017
DOI: 10.1186/s40902-017-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of dystrophic calcification in the masseter muscle

Abstract: BackgroundDystrophic calcification can occur in any soft tissue with the absence of a systemic mineral imbalance and is often associated with trauma, infection, or inflammation. It is easily found in the site of the heart and skeletal muscles and rarely appears in the head and neck area.Case reportWe present a rare case of multiple calcified masses in the left masseter muscle of a 26-year-old female with a history of trauma in the area. In computed tomography, multiple radiopaque masses were observed inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is thought to be related to apoptotic cells failing to regulate intracellular calcium and precipitation of calcium phosphate crystals, which accumulate in the wound. 9 , 10 Unlike the elevated serum levels seen in metastatic calcification, the serum levels of calcium and phosphate will be normal in the presence of dystrophic calcification. Additionally, other internal organs will not be affected because the calcification will typically be centered at the wound and ulcer area, which supports the dystrophic, rather than the metastatic, calcification diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be related to apoptotic cells failing to regulate intracellular calcium and precipitation of calcium phosphate crystals, which accumulate in the wound. 9 , 10 Unlike the elevated serum levels seen in metastatic calcification, the serum levels of calcium and phosphate will be normal in the presence of dystrophic calcification. Additionally, other internal organs will not be affected because the calcification will typically be centered at the wound and ulcer area, which supports the dystrophic, rather than the metastatic, calcification diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Calcinosis is a complication characterized by calcium deposition in soft tissues, usually associated with trauma, infection, or inflammation. This process is poorly known in the literature, and there is still no stipulated protocol for its treatment (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the reviewed studies failed to provide long enough follow-up period (the longest was 2.5 years [18]), to conclude any valuable prediction. Kim et al [33] reported no abnormal reaction in hypersensitivity and cytotoxicity test after using particulated dentin. Complications such as infections and inflammatory reactions of sinus mucosa were not encountered in any of the studies reviewed in the present paper.…”
Section: Discussionmentioning
confidence: 99%